The Effect of Using Task-based Language Teaching on Students' Reading Comprehension at SMAN 1 Bangkinang Kota - Rina Gusman Putri; Ratmanida Ratmanida (Journal of English Language Teaching, 2021)
This research is quasi-experimental research. The purpose of this research is to find out the effect of using task-based language teaching on students’ reading comprehension at SMAN 1 Bangkinang Kota. The research sample was 36 students of class X Mipa 1 as the experimental class and 36 students of class X Mipa 3 as the control class. The instrument of this research was reading test that was conducted into two tests, pre-test and post-test. The instrumentation was created into 20 multiple questions. Based on the data analysis by using Paired Sample T-test in SPSS 23 for windows, the mean of pre-test score in the experimental class was 51.2 while the mean of post-test score in experimental class was 81.2. It can be concluded that the students’ who are taught by using task-based language teaching as teaching method are better than students who are taught by using conventional method. The significance of the test is 0.000 which is lower than the significance level that is 0.05 with 5% of degree. Moreover, it is also found that the students’ score is improving especially for the students in the experimental class which gained 30.0 of their average score.